Meet the good child. 'Childing' practices in family food co‐shopping. (10th July 2016) - Gram, Malene; Grønhøj, Alice
Abstract: This article explores 'childing' pratices in relation to family supermarket shopping in Denmark. 'Parenting' practices have been explored for long but little attention has been given to how children strive to be 'good' children, who live up to certain standards and recognize what they perceive to be appropriate child and parental behavior. The study takes a practice theoretical perspective, building on previous research on family consumption, and draws empirically on 35 interviews with 5–6 year‐olds and 13 family interviews. Findings show that the children recognize the position of 'the good child' and most often prefer to take on this position, which is confirmed by their parents. The children can describe how 'the good child'—in their eyes—should behave. They prefer consensus and not being embarrassing or embarrassed. The study concludes that the children are strongly immersed in social norms and family practices, and that the Danish national/cultural context probably reinforces these children as independent consumers, who are well aware of the requirements of the consumer role. Childing practices are a standard with know‐how and rules that these children argue they live by—at least most of the time—and by which they judge their own behavior and that of other children.